Fatal first edition - McKinlay, Jenn (McKinlay, Jenn. Library lover's mysteries., 2024)
"Briar Creek Library director Lindsey Norris and her husband, Sully, are at a popular library conference in Chicago to hear book restoration specialist Brooklyn Wainwright give a keynote address. After the lecture, Lindsey looks under her seat and finds a tote bag containing a first edition of Patricia Highsmith's Strangers on a Train, inscribed to Alfred Hitchcock. Brooklyn determines the novel is one of a kind and quite valuable, so Lindsey and Sully return the book to the conference director, not wanting to stir up any trouble. But just hours after the pair boards the train back to Connecticut, rumors that the Highsmith novel has gone missing buzz amongst the passengers, and they soon find the conference director murdered in his private compartment. And worse--the murderer planted the book in Lindsey and Sully's room next door, making them prime suspects. Now, they must uncover the murderer and bring them to the end of their line, before they find themselves booked for a crime they didn't commit"--